2022
DOI: 10.3390/vaccines10091386
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Vaccination of Older Adults with an MF59-Adjuvanted Quadrivalent Influenza Vaccine Compared to Other Available Quadrivalent Vaccines in Germany

Abstract: Enhanced quadrivalent influenza vaccines that include an adjuvant (aQIV) or a high dose of antigen (QIV-HD), which stimulate a stronger immune response in older adults than the standard vaccine (QIVe), are now approved. The objective of this research is to compare available vaccines and determine the cost-effectiveness of immunizing persons aged 65 years and above with aQIV compared to QIVe and QIV-HD in Germany. A compartmental transmission model calibrated to outpatient visits for influenza in Germany was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…In addition, aQIV fell below the Spanish cost-effectiveness threshold in this study [ 21 ]. The findings of both modeled comparisons—aQIV vs. HD-QIV and aQIV vs. QIVr—are consistent with cost-effectiveness studies of aQIV conducted in Europe and Latin America [ 45 , 46 , 47 , 48 ]. A study in Germany used a compartmental transmission model to predict the number of medically attended infections among adults ≥65 years vaccinated with aQIV or HD-QIV and assumed the rVE range of –2.5% to 8.9% for aQIV vs. HD-QIV, based on data from the meta-analysis of aTIV and HD-TIV comparisons [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, aQIV fell below the Spanish cost-effectiveness threshold in this study [ 21 ]. The findings of both modeled comparisons—aQIV vs. HD-QIV and aQIV vs. QIVr—are consistent with cost-effectiveness studies of aQIV conducted in Europe and Latin America [ 45 , 46 , 47 , 48 ]. A study in Germany used a compartmental transmission model to predict the number of medically attended infections among adults ≥65 years vaccinated with aQIV or HD-QIV and assumed the rVE range of –2.5% to 8.9% for aQIV vs. HD-QIV, based on data from the meta-analysis of aTIV and HD-TIV comparisons [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 76%
“…The findings of both modeled comparisons—aQIV vs. HD-QIV and aQIV vs. QIVr—are consistent with cost-effectiveness studies of aQIV conducted in Europe and Latin America [ 45 , 46 , 47 , 48 ]. A study in Germany used a compartmental transmission model to predict the number of medically attended infections among adults ≥65 years vaccinated with aQIV or HD-QIV and assumed the rVE range of –2.5% to 8.9% for aQIV vs. HD-QIV, based on data from the meta-analysis of aTIV and HD-TIV comparisons [ 44 , 45 ]. In different modeling scenarios conducted based on influenza severity and the rVE range of –2.5% to 8.9% for aQIV vs. HD-QIV, aQIV was consistently shown to be cost saving because the unit cost of aQIV (EUR 19.21) was less than half that of HD-QIV (EUR 40.55), while vaccine effectiveness was similar.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To our knowledge, this is the first evaluation of the cost-effectiveness of an adjuvanted QIV for older adults in Ireland. Previous studies in other countries have also shown aQIV to be more cost-effective for use in older adults compared with standard-dose QIVs [ 18 , 19 , 21 , 28 , 42 ]. While the degree of cost-effectiveness varied with the vaccine price, cost benefits were mainly driven by the higher vaccine effectiveness of aQIV in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis from Germany, adjuvant and high-dose influenza vaccines achieved similar clinically results (hospitalisations, deaths, etc . ), but the adjuvant vaccine was more cost saving compared to high-dose vaccine [ 72 ]. None of the mentioned studies suggested any clinically relevant changes in safety beyond what is known.…”
Section: Influenza Vaccinementioning
confidence: 99%